2015
DOI: 10.21776/ub.wacana.2015.018.01.1
|View full text |Cite
|
Sign up to set email alerts
|

Implementation of Compulsory Study 12 Year Policy to Increase Education Quality in Kudus Regency

Abstract: Education is an important instrument in improving the

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 0 publications
0
2
0
Order By: Relevance
“…In Indonesia, the government introduced a twelve-year compulsory education program aimed at eliminating ignorance. However, this program has not yet achieved its expected outcomes (Pairulsyah and Suwarno, 2022;Lestari et al, 2015). Research by Ahmadi et al (2020), Djohar et al (2020), and Malik (2018) showed that the need for school has been felt by the majority of the community.…”
Section: *Thementioning
confidence: 99%
“…In Indonesia, the government introduced a twelve-year compulsory education program aimed at eliminating ignorance. However, this program has not yet achieved its expected outcomes (Pairulsyah and Suwarno, 2022;Lestari et al, 2015). Research by Ahmadi et al (2020), Djohar et al (2020), and Malik (2018) showed that the need for school has been felt by the majority of the community.…”
Section: *Thementioning
confidence: 99%
“…ISSN: 2656ISSN: -1174 International Standard School; National Examination; and Compulsory Basic Education Policy. All these policies are formulated to improve the national education quality (Lestari, Wijaya, & Rochmah, 2015).…”
Section: Introduction Research Backgroundmentioning
confidence: 99%